PERANCANGAN WEB DESAIN CV. RANGKIANG TENUN KUBANG KAB. 50 KOTA - MULIANDRA, Dra. Zubaidah, M.Sn., Ishakawi, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
The Purpose of the design of web design CV. Rangkiang this is (1) to design a display web design to CV. Rangkiang as media promotion and communication, (2) make the layout that is effective and efficient and aesthetically pleasing, (3) provide an aesthetic element to the website so exciting to look for information about your CV. Rangkiang. Design is a Media President in the form of web design CV. Rangkiang, in addition to major media is also made the Media Support in the form of print media, such as: The posters, X Banner, a name, Brochures, Calender, Sticker, Pin, and The key holder.Keywords: Web Design, Design, CV. Rangkiang